Social Roles in Green Book Dialogue: An Ethnography of Communication Analysis Using SPEAKING Framework - Rahmalia Anas, Adinda Asmarani (STKIP PGRI Tulungagung, 2025)
This study explores how ethnography of communication in the movie Green Book (2018) reflects social roles through the characters’ dialogue. Using Dell Hymes’ SPEAKING framework, it examines how the characters’ communication reveals cultural values and navigates social dynamics between Dr. Don Shirley, an African-American pianist, and Tony Lip, his Italian-American driver, during their road trip through racially segregated America in the 1960s. A content analysis method is employed to analyze key dialogues, focusing on elements like Setting, Participants, Ends, Act Sequence, Key, Instrumentalities, Norms, and Genre. The findings show that differences in social roles based on race, class, and power are constructed and negotiated through language use in the conversation. Dr. Shirley used formal and polite language to assert his authority while dealing with being treated unfairly in society. On the other hand, Tony’s casual and resistant way of speaking reflected his working-class background. These differences in how they communicate highlight the power struggles and cultural tensions in their social roles. These insights reveal how the film uses language to portray the complexities of communication across cultures, allowing viewers to better understand the interplay of social roles, race, and class in interpersonal relationships.